Revolutionizing Education Impact of Innovative Teaching and Learning Technologies - Herawan, Endang (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Education is undergoing a profound transformation driven by innovative teaching and learning technologies. These advancements are redefining traditional educational methods, fostering personalized learning experiences, and bridging gaps in access to quality education. This article explores the impact of emerging technologies such as artificial intelligence, virtual reality, and adaptive learning platforms on modern education. By enhancing student engagement, enabling real-time feedback, and supporting diverse learning styles, these tools empower both educators and learners. Furthermore, the integration of technology in classrooms promotes global collaboration and prepares students for a rapidly evolving digital world. While challenges such as accessibility, training, and ethical concerns persist, the potential of these innovations to revolutionize education is undeniable. This study emphasizes the importance of adopting a forward-thinking approach to ensure technology enhances learning outcomes and shapes a future-ready generation.